Perencanaan Lingkungan Pendidikan Islam di SMA Arrahman Depok - Devvi Diana Putri; Maemunah Sa'diyah; Mas’udin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
Education is a conscious and planned effort to obtain a conducive, safe and comfortable learning atmosphere and process. An educational institution is a place for someone to obtain an education in which there are students, educators, educational staff. All existing components, including objects and plants, are referred to as the environment. The educational environment needs to be supported to achieve the planned goals. The need for planning in the world of education so that it does not become a vital thing and failure. Educational environment planning in the form of physical, social and academic environments. This educational research method uses qualitative, researchers analyze and describe the results obtained. The research results were obtained through interviews, documentation and observations carried out at Arrahman High School, Depok. The results of the research state that digital-based schools do not forget Islamic values ​​in them. Education teachers and other staff try to integrate science and technology and IMTAQ on an ongoing basis. This is because the school is under the auspices of the Islamic Education Foundation. Recommendation for other researcgers can be more specific in discussing environmental elements.